Evaluasi Kualitas Layanan Pada Aspek Before Sales Service, After Sales Service, dan Kepuasan Pelanggan (Studi Pada E-Commerce XYZ) - Ratna Khansa Anantika; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-Commerce XYZ is one of the most highly ranked E-Commerce sites from year to year, but it can not be ranked top. It shows that the importance of user satisfaction in influencing the quality of service is expected to improve the ranking of E-Commerce XYZ. Research has tested on two quality services, ie Before Sales Service and After Sales Service by using E-S-QUAL with Linear Regression analysis and Rank Spearman. Before Sales Service acts as a user perception before transacting to be researched on an E-S-QUAL scale, while After Sales Service acts as a perception when the user has transacted and goods to the hand that will be examined on an E-Recs-QUAL scale. Data collection technique is done by distributing questionnaires with the number of samples of 100 respondents who have characterized the ever visited and transacted at E-Commerce XYZ. The results showed Efficiency, Fulfillment, System Availability, Privacy, Responsiveness, Compensation, and Contact respectively have a significant relationship to satisfaction. The results of the research together also shows Before Sales Service and After Sales Service has a significant relationship to satisfaction.